The Combination of High Levels of Adiponectin and Insulin Resistance Are Affected by Aging in Non-Obese Old Peoples - Muratsu, Jun; Kamide, Kei; Fujimoto, Takashi; Takeya, Yasushi; Sugimoto, Ken; Taniyama, Yoshiaki; Morishima, Atsuyuki; Sakaguchi, Katsuhiko; Matsuzawa, Yuji; Rakugi, Hiromi (Frontiers in Endocrinology, 2022)
Background Adipokine dysregulation is a key feature of insulin resistance and a metabolic syndrome associated with obesity. Low adiponectin levels are associated with higher risks of cardiovascular diseases (CVD). However, high adiponectin levels have also been associated with increased all-cause and cardiovascular mortality in the elderly. This adiponectin paradox has yet to be clarified, which has hindered our understanding of the biological role of adiponectin. Adipokine dysregulation and insulin resistance are also associated with energy-deprivation conditions, such as frailty in old age. The objective of this study was to investigate the association between plasma adiponectin and insulin resistance using the homeostasis model assessment for insulin resistance (HOMA-IR) classified by age. In particular, we sought to determine the factors of the subjects associated with both high adiponectin levels and HOMA-IR (H-adiponectin/H-HOMA) and high adiponectin levels and low HOMA-IR (H-adiponectin/L-HOMA). Methods The eligible subjects in this cross-sectional study were 33,216 individuals who had undergone health checkups at the Physical Checkup Center of Sumitomo Hospital between April 2008 and December 2018. After excluding 26,371 individuals who were under 60 years old, 529 who had been taking medications for diabetes mellitus, and 690 with missing data, the present study included 5,673 (3,467 males, 2,206 females) subjects with no missing data. The relationship between serum adiponectin levels and HOMA-IR was assessed using logistic regression models adjusted by clinically relevant factors. Results In the multivariable logistic regression analysis, age and low BMI were shown to positively correlate with the characteristics of H-adiponectin/H-HOMA. In females, systolic blood pressure was also shown to be an associated factor. Conclusion In conclusion, this study showed that aging or a low BMI may contribute to high adiponectin levels and insulin resistance.